In vitro Human Cartilage Tissue System for Putative Disease Model. - Sun, Lin. (2017)
Abstract: Cartilage tissue engineering is a promising approach for the formation of in vitro tissue models. Currently, progress in tissue engineering has been made in reproducing functional tissue implants and disease models, and on predicting how the functional properties of chondrocytes and the extracellular matrix change in response to physical perturbations of the tissue models. In order to gain insight into specific diseases, such as osteoarthritis, improved in vitro cartilage tissue constructs are required. The goal of the present program was to develop in vitro tissue systems that were closer representatives of cartilage-related diseases, such as osteoarthritis, in order to be able to exploit these systems for future study of disease formation and for drug screening. Specifically, in the first part of the studies, the design of a tissue engineered cartilage system mimicking inflammatory conditions in joints is described, as a step toward understanding the response of primary human chondrocytes and extracellular matrix components to inflammatory mediators. From these experiments, a broad spectrum of inflammatory mediators from macrophages was applied and osteoarthritis-like symptoms were observed at the cellular and tissue level. In the second part of the studies, a strategy was established to improve the redifferentiation of human primary chondrocytes and cartilage-specific matrix accumulation in engineered cartilage. In the third part of the studies, the cartilage constructs, together with a specialized bioreactor, was assessed for the study of cyclic compressive loading on the cartilage at the cellular and tissue level as a physiologically-relevant approach to use the tissue model for the study of osteoarthritis. In the last part of studies, physiochemical properties of silk fibroin scaffolds prepared under different conditions were characterized in terms of morphology, degradation rate, porosity and mechanical properties. The goal was to relate the features of the biomaterial matrix to tissue remodeling, in the context of normal vs. disease states. In conclusion, the strategies developed in this thesis offer a new platform for cartilage tissue engineering and provide a basis for future work in the study of cartilage related diseases using more refined cartilage tissue models in vitro.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: David Kaplan.; Committee: Li Zeng, Yongzhong Wang, Catherine Kuo, and Kyongbum Lee.; Keyword: Biomedical Engineering.